PENGARUH KOMPENSASI, KEPUASAN KERJA, DAN PENGEMBANGAN KARIR TERHADAP RETENSI KARYAWAN DI PT ARTHA DEVATA UTAMA - Devina ningsih; Gde Bayu Surya Parwita; Made Ika Prastyadewi (VALUES, 2024)
The purpose of this research is to determine the effect of compensation, job satisfaction, and career development on employee retention at PT Artha Devata Utama. The population of this research is all employees of PT Artha Devata Property, totaling 51 people. The method used in determining the sample is the nonprobability sampling method. The sample in this research was all employees of PT Artha Devata Utama, totaling 51 people. Data collection in this research was carried out using interview and questionnaire methods. The analysis techniques used are the classical assumption test, multiple linear regression analysis and model feasibility tests consisting of the coefficient of determination test, multiple correlation, F test and t test. The research results show that compensation, job satisfaction, and career development have a positive and significant effect on employee retention at PT Artha Devata Utama. This means that the higher the compensation given, the higher the job satisfaction felt and the higher the career development felt by PT Artha Devata Utama employees, the more employee retention will increase.